Jessi Ramsey, pet-sitter - Martin, Ann M., 1955-; Crenshaw, Ellen T. (Baby-sitters Club (Graphix (Firm)), 2025)
"The Mancusis don't have any kids... but they sure do have a lot of pets! So when they're desperate for a sitter, who do they call? The Baby-sitters Club! Kristy feels pretty sure that the BSC does not pet-sit. But Jessi has always liked animals, and she talks Kristy into being okay with her taking the job. With snakes on the loose and sick hamsters, Jessi's got plenty of pet-sitting troubles, and things don't get any easier when she and her friends get into a big fight. Will Jessi be able to handle her pet-sitting job when things are going wrong with the baby-sitters, too?"--